Characteristics of Curious Minds: Evidence from Interviews with Renowned Experts in Five Curiosity-Dominant Fields - Menucha Birenbaum; Fadia Nasser-Abu Alhija; Hany Shilton; Helena Kimron; Neria Shahor; Rovena Rosanski (Education Sciences, 2024)
Semi-structured interviews were conducted with 50 renowned experts from five curiosity-dominant professional fields (scientists, inventors (high-tech entrepreneurs), artists, explorers, and therapeutic professionals). The five-dimensional curiosity framework proposed by Kashdan and colleagues (comprising joyous discovery, deprivation sensitivity, social curiosity, stress (uncertainty) tolerance, and thrill-seeking) was adopted. The purpose was to explore nuances of curiosity manifestations expressed by the subjects in their own words and related personality and contextual attributes. A directed approach to content analysis was applied to code the interview data; qualitative methods were employed for data analysis, complemented by quantitative ones. Insights gained from the findings regarding the curiosity construct, focusing on differences among the groups in regard to aspects of social curiosity and effects of uncertainty tolerance and thrill-thinking, were discussed, followed by implications for cultivating curious minds.